Measures to inhibit the growth of apple tree top with the `gala´ variety - Matjaž BEBER (Acta Agriculturae Slovenica)
In Fruit Research Center Maribor different methods of less vigorous growth of apple tree top with the variety `Gala´ were conducted during the period from 2010 to 2013: applying a coating of the central leader at a height of 2.2 m with 2 % solution of growth regulator NAA (Luxan Late – Val) and plant resin, the use of the growth retardant Regalis (2 times), of replacing the the top of the tree with the highest appropriate bent branch, removal of new shoots 28 days after flowering (tearing) and the June cut after the completion of the primary growth. Increment of annual shoots and harvest in the top (over 2.2 m) was followed. Most commonly used practices, the June cut and tearing of young shoots resulted in the strongest growth in the top. The vigour of the top of the tree was the best reduced by the use of plant growth regulators (Regalis and NAA top coating) and replacing the top of the tree. The highest yield of the top of the tree was achieved by using Regalis, meanwhile tearing of the young shoots gave the lowest yield. The replacing the top of the tree is suitable measure for organic production, because it successfully reduces the vigour of the tree top without the use of growth regulators.